Explaining purchase intention in live streaming commerce: A technology acceptance model perspective - Septiani, Dina; Putri, Elsanty; Pradika, Mohammad Fawaid (Universitas Bunda Mulia, 2026)
The development of technology will bring changes to people's lives, one of which is in the business sector, business actors are able to compete and market the products they sell more easily through E-commerce. Technology also brings the rapid flow of E-commerce with various features, one of which is the live streaming feature. Shopee Live is one of the famous live streaming features of E-commerce Shopee. This feature helps sellers and customers directly or in real-time. Live streaming can also encourage consumer interest in purchasing products to be purchased because they get detailed service and product explanations from streamers or sellers. Glasses, which are fashion products, are usually sold offline, can now be marketed online using the live streaming feature, This study analyzes the effect of Live Streaming (X) on Purchase Interest (Y) in eyeglass products through E-commerce Shopee using an explanatory quantitative research method that describes the relationship between variables. The measuring instrument used was the distribution of questionnaires to 100 respondents with a purposive sampling technique. Based on the processed data obtained through the hypothesis test (T test), the t-count value was 4.395> t-table 1.984. This means that this study has a significant influence between variables X and Y. This means that live streaming shopee live has an effect on consumer purchasing interest in Djava Optik eyeglass products. Through the credibility of the live host, the richness of the existing media and the interactivity of the live streaming broadcasts provided, consumer purchasing interest in Djava Optik eyeglass products is increasing.